Exploring the Women in College Coaching Report Card for 2023-24 - LaVoi, Nicole M.; Goorevich, Anna (My University, 2024)
In this episode, Dr. Nicole M. LaVoi talks with Anna Goorevich as they dive into the Tucker Center's 2023-2024 Women in College Coaching Report Card, created in collaboration with WeCOACH. Together, they explore the latest data, discussing the successes, challenges, and future of the Division I women’s coaching landscape. Listeners will hear about which sports and institutions are leading the pack and which ones are still falling short in promoting women in coaching.
Runtime 25:01